Evidence for partial pharmaceutical reversal of the cancer anorexia–cachexia syndrome: the case of anamorelin. Issue 4 (30th August 2015) - Anker, Stefan D.; Coats, Andrew J. S.; Morley, John E.
Abstract: A major component of the cancer anorexia‐cachexia syndrome is a decline in food intake. Up until now none of the drugs that improve appetite also improve skeletal muscle. Recent studies have suggested that the oral ghrelin‐analog, anamorelin, increased food intake and muscle mass. Unfortunately, it does not increase muscle power. Its regulatory future is uncertain, although it has important clinical effects.